Cu submicroparticles catalyzed reduction of 3‐nitro‐4‐methoxyacetanilide to 3‐amino‐4‐methoxyacetanilide in water. (22nd March 2017) - Feng, Yonghai; Yin, Hengbo; Yan, Xiaobo; Meng, Minjia; Mi, Jianli; Wang, Aili
Abstract: 3‐nitro‐4‐methoxy acetanilide (NMA) was selectively reduced to 3‐amino‐4‐methoxy acetanilides (AMA) with metallic Cu submicroparticles as the H‐transfer catalyst in NaBH4 solution. The metallic Cu submicroparticles were prepared by the wet chemical reduction method and characterized by SEM, XRD, and XPS techniques. The catalytic activity of Cu submicroparticles in the reduction of NMA was significantly affected by the particle sizes of Cu submicroparticles. The catalyst of Cu submicroparticles with an average particle size of 0.36 µm contributes to an AMA selectivity of 96.1 % at the NMA conversion of 100 % after reacting at 303 K for 40 min. The Cu submicroparticles show better catalytic activities than the Cu microparticles in the reduction of NMA to AMA probably due to the low reaction orders and the low activation energy of Cu submicroparticles for the reduction of NMA. Abstract : Selective catalytic reduction of NMA to AMA over Cu submicroparticles.